COMPARISON OF TAKLIFI LAW ON THE VIEWS OF ABU HAMID AL-GHAZALI AND ABDUL HAMID BIN AL-HUSAIN AL-SHARWANI REGARDING SHARING HAIR AND CUTTING NAILS WHEN JUNUB - Ira Maulidatul Ula; Amin Said Husni (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
This thesis, titled